2021
DOI: 10.46405/ejms.v3i1.251
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of Pediatric Both Bone Fractures Fixed with Titanium Elastic Nails: : A Hospital Based Study

Abstract: Background: Successful treatment of both bone fractures depends on the restoration of normal alignment and full recovery of range of motion that can be achieved by either closed reduction and casting or surgical intervention. Number of surgical treatment modalities have been mentioned for unstable pediatric both bone fractures that includes Kirschner wire fixation, plating, external fixation and elastic intramedullary nailing Methods: This was descriptive cross-sectional study performed from January 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(28 reference statements)
2
2
0
Order By: Relevance
“…The improvement in range of motion was significant over time in patients who underwent intramedullary nailing. The overall complication rate in our study was 6%, which is similar to the rates described by Kc et al [ 21 ]. According to criteria by Price et al, 90% showed excellent outcomes, 7% showed good outcomes, and 3% showed fair outcomes [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The improvement in range of motion was significant over time in patients who underwent intramedullary nailing. The overall complication rate in our study was 6%, which is similar to the rates described by Kc et al [ 21 ]. According to criteria by Price et al, 90% showed excellent outcomes, 7% showed good outcomes, and 3% showed fair outcomes [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study are consistent with the clinical and radiological results of previous studies of Open Reduction and Internal Fixation (ORIF) of fracture of both the radius and ulna [ 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Participants in our study had a mean age of 8.8 years, ranging between 0 and 15 years, with 53% of patients aged between six and 10 years.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The restoration of supination and pronation is the primary determinant of successful outcomes. The majority of earlier investigations on pediatric forearm fractures revealed favorable results during follow-up [7,8].…”
mentioning
confidence: 99%